Training on the Production of Eco-Friendly Organic Detergent Based on Hibiscus tiliaceus Leaf Extract at SMAN 3 Palu - Dinalia Dinalia; Arif Ahmadi (Pelita Eksakta, 2026)
The increasing use of synthetic detergents has contributed to water pollution and environmental degradation, highlighting the need for safer and more sustainable cleaning alternatives. This community service program aimed to train students of SMAN 3 Palu in producing an eco-friendly detergent derived from Hibiscus tiliaceus (daun waru) extract while strengthening their understanding of basic chemical concepts. The activities consisted of theoretical counseling, demonstration of the production process, hands-on practice, and evaluation through a 3-point Likert scale questionnaire. The results indicate that students were able to follow each stage of the procedure, including extraction, formulation, pH testing, and foam performance evaluation. Participant responses showed a highly positive assessment, particularly regarding the clarity of material delivery, adequacy of tools and materials, and overall satisfaction with the program. The training also fostered creativity and environmental awareness by introducing natural ingredients as an alternative to synthetic detergents. In conclusion, this program effectively enhanced students’ knowledge, practical skills, and environmental consciousness and has strong potential to be developed as a continuous educational initiative within the school.